Internalization of the Character Value of Self-Confidence in Children with Special Needs Through Sports Activities at Karawang District State SLB - Vania Salsabila Lupi; Cik Suabuana; Warlim Warlim (Jurnal Pendidikan Edutama, 2024)
This research discusses innovative strategies in building self-confident character in children with special needs through sports activities at the Karawang Regency State Special School. Using a qualitative approach, this research reveals the planning, process, obstacles and evaluation of the internalization of character values in children with special needs. Teachers play an active role in identifying character values, preparing plans, and integrating them into the hidden curriculum. Even though evaluations tend to be subjective, sports activities at the Karawang Regency State Special School have been proven to have a positive impact on character development, especially in the aspects of adaptation, communication and interaction. Obstacles involve diverse student characteristics and sports teacher limitations. This research contributes to further understanding of character formation in children with special needs and provides recommendations for increasing the effectiveness of the sports curriculum in the context of character education.